Improved boomerang attacks on round‐reduced SM3 and keyed permutation of BLAKE‐256. Issue 3 (1st May 2015) - Bai, Dongxia; Yu, Hongbo; Wang, Gaoli; Wang, Xiaoyun
Abstract : In this study, the authors study the security of hash functions SM3 and BLAKE‐256 against boomerang attack. SM3 is designed by Wang et al . and published by Chinese Commercial Cryptography Administration Office for the use of electronic certification service system in China. BLAKE is one of the five finalists of the NIST SHA‐3 competition submitted by Aumasson et al . For SM3, they present boomerang distinguishers for the compression function reduced to 34/35/36/37 steps out of 64 steps, with time complexities 2 31.4, 2 33.6, 2 73.4 and 2 192, respectively. Then, they show some incompatible problems existed in the previous boomerang attacks on SM3. Meanwhile, they launch boomerang attacks on up to 7‐ and 8‐round keyed permutation of BLAKE‐256, which are the first valid 7‐round and 8‐round boomerangs for BLAKE‐256. Especially, since the author's distinguishers on 34/35‐steps compression function of SM3 and 7‐round keyed permutation of BLAKE‐256 are practical, they are able to obtain boomerang quartets of these attacks. As far as they know, these are the best results against round‐reduced SM3 and BLAKE‐256.